Interaction of Skeletal and Left Ventricular Mass in Older Adults with Low Muscle Performance. Issue 1 (16th September 2020) - Pelà, Giovanna; Tagliaferri, Sara; Perrino, Felice; Bussolati, Giacomo; Longobucco, Yari; Zerbinati, Luna; Adorni, Elisa; Calvani, Riccardo; Cesari, Matteo; Cherubini, Antonio; Bernabei, Roberto; Di Bari, Mauro; et al.
Abstract : BACKGROUND: It was recently hypothesized the existence of "cardiac‐skeletal muscle axis." However, the relationship between skeletal muscle mass (SMM) and left ventricular mass (LVM) has never been investigated in the specific group of older individuals with low skeletal mass and physical performance. We tested this hypothesis in the SPRINT‐T (S arcopenia and P hysical Frailty IN older people: multicomponenT Treatment strategies T rial) population using LVM as independent variable and SMM as dependent variable. METHODS: SMM was assessed by dual‐energy X‐ray absorptiometry scan and expressed as appendicular lean mass (ALM), and LVM was estimated through echocardiography. Low ALM was defined according to Foundation for the National Institutes of Health Sarcopenia Project criteria, and Short Physical Performance Battery (SPPB) was used to assess physical performance. RESULTS: The population consisted of 100 persons (33 men and 67 women), aged 70 years or older (mean age = 79 ± 5 years) with low ALM and SPPB ranged between 3 and 9, suggestive of physical frailty. Charlson Comorbidity Index median score was 0. Mean value of LVM was 193 ± 67 g, indexed LVM/body surface area (LVM/BSA) was 112 ± 33 g/m 2, and cardiac output (CO) was 65 ± 19 L/min. ALM was strongly and positively correlated with LVM (r = 0.54602; P  < .0001), LVM/BSA (r = 0.30761; P  < .002), CO (r = 0.49621; P  < .0001), body mass index (BMI) (r = 0.52461; P  < .0001), sex (r = 0.77; P  < .001), fat mass (r = 0.38977; P  < .0001), and hemoglobin (Hb) (r = 0.26001; P  < .01). In the multivariate analysis, LVM (β = .019 ± .005; P  < .0001), CO (β = .038 ± .016; P = .019), BMI (β = .286 ± .051; P  < .0001), and Hb (β = .544 ± .175; P = .0025) remained associated to ALM. CONCLUSIONS: In a sample of older persons with low muscle mass and physical performance, LVM was positively and significantly correlated with ALM, independently from blood pressure, physical activity, and other potential confounders. Future studies are needed to address the effect of interventions targeting LVM and SMM.